PERANCANGAN APLIKASI SMS (SHORT MESSAGE SERVICE) DENGAN ENKRIPSI TEKS MENGGUNAKAN ALGORITMA BLOCK CIPHER AES (ADVANCED ENCRYPTION STANDARD) BERBASIS MOBILE PADA PLATFORM ANDROID - Irwan, Irwan (Jurusan Informatika Universitas Tanjungpura, 2013)
Abstract - In recent several years, there was a rapid development in mobile phone technology. One is the development of smart phone with many features and also complex operating system that similar to a computer. Although smart phones have many features that included in the operating system, but long or short messaging service known as SMS is still popular in use. SMS feature that still exist till today, bring out the question about the safety of information if someone wants to send a confidential information via SMS facility. The ease of exchanging information via SMS is misused by some people. Some people with a variety of ways to try to steal information that's illegal. Therefore, we need a way to secure the information that is confidential and important. Encryption process can be used to improve the SMS text message levels of information security. Currently, AES (Advanced Encryption Standard) is used as a standard for cryptographic algorithms. Therefore, it can be developed an SMS application with a text encryption using AES algorithm. Mobile-based applications built on the Android platform. The test results showed that the application can perform encryption of short messages with text to a particular destination number and can not decrypt the encrypted message. Application can help users to send short messages in a secure, fast, and easy.Â Â